Nanostructured Ti29.7Ni50.3Hf20 high temperature shape memory alloy processed by high-pressure torsion. (1st September 2020) - Shuitcev, A.; Gunderov, D.V.; Sun, B.; Li, L.; Valiev, R.Z.; Tong, Y.X.
Abstract: High-pressure torsion (HPT) processing under a pressure of 6.0 GPa was applied to Ti29.7 Ni50.3 Hf20 (at.%) alloy. Two types of structure were observed after HPT with 3 revolutions: first one is the mixture of amorphous phase and retained nanocrystalline; second is the alternating bands of amorphous phase and high defect density crystalline. As a result, post deformation annealing (PDA) at 500−700 °C leads to the non-uniform distribution of martensite and parent phase grains. The grains of martensite are twice larger compared to that of parent phase. The nanocrystalline and ultrafine grains form after annealing at 500−600 °C and 700 °C, respectively. The twinning mechanism does not change with the reduction of martensitic grains up to ∼35 nm. The relationship between strength and grain size in Ti29.7 Ni50.3 Hf20 alloy obeys the classical Hall-Petch relationship with a coefficient of 10.80 ± 0.39 GPa nm 1/2 .